Long-term trend analysis in climate variables and agricultural adaptation strategies to climate change in the Senegal River Basin - Djaman, K.; Balde, A.B.; Rudnick, D.R.; Ndiaye, O.; Irmak, S. (Wiley, 2017)
The objectives of this study were to investigate the trend in annual precipitation, sunshine duration, wind speed (u 2), and annual and monthly minimum temperature (T min), maximum temperature (T max), and relative humidity (RH) and the adaptation strategies for the Senegal River Basin. Annual precipitation, T min, T max, RH, sunshine duration, and u 2 for the period of 1950–2000 recorded at St‐Louis, Bakel, Dagana, Fanaye, Podor, and Matam have been analysed using the Mann–Kendall test and Sen's slope estimator. Annual precipitation varied with location from 900 mm registered in 1967 at Bakel to 32 mm obtained at Dagana in 1986. A significant decreasing trend (p < 0.001) in precipitation was observed at Podor, Dagana, Matam, Bakel, and St‐Louis. A non‐significant decreasing trend in annual precipitation was observed at Fanaye Dieri. There was a significant increasing trend (p < 0.001) in T max and T min at all locations. Sunshine duration had a significant decreasing trend at Podor, Matam, and St‐Louis at the rate of 0.27, 0.28, and 0.35 h decade−1, respectively. RH and u 2 have differences in their trends, with the first one showing a strong and significant decrease and u 2 with less significance in their trends. The trend analysis in the climate variables revealed a change in climate that necessitates some specific actions for resources management sustainability and conservation.